2018
DOI: 10.1158/1078-0432.ccr-17-2542
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Resolved and Quantitative Analysis of VISTA/PD-1H as a Novel Immunotherapy Target in Human Non–Small Cell Lung Cancer

Abstract: Purpose Determine the localized expression pattern and clinical significance of VISTA/PD-1H in human NSCLC. Experimental Design Using multiplex quantitative immunofluorescence (QIF), we performed localized measurements of VISTA, PD-1 and PD-L1 protein in 758 stage I-IV NSCLCs from 3 independent cohorts represented in tissue microarray format. The targets were selectively measured in cytokeratin+ tumor epithelial cells, CD3+ T-cells, CD4+ T-helper cells, CD8+ cytotoxic T-cells, CD20+ B-lymphocytes and CD68+ t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
160
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(177 citation statements)
references
References 34 publications
12
160
1
4
Order By: Relevance
“…Similarly, VISTA expression is up‐regulated after ipilimumab (anti‐CTLA‐4) therapy in prostate cancer . In addition, VISTA expression seems to correlate with PD‐1/PD‐L1 expression; for example, in colon cancer, NSCLC and gastric cancer . Overall, these data on the expression of VISTA in human cancer are highly supportive that targeting of VISTA as part of immunotherapeutic strategies may be of great value.…”
Section: Vista Expression In Tumor‐infiltrating Immune Cellsmentioning
confidence: 82%
See 1 more Smart Citation
“…Similarly, VISTA expression is up‐regulated after ipilimumab (anti‐CTLA‐4) therapy in prostate cancer . In addition, VISTA expression seems to correlate with PD‐1/PD‐L1 expression; for example, in colon cancer, NSCLC and gastric cancer . Overall, these data on the expression of VISTA in human cancer are highly supportive that targeting of VISTA as part of immunotherapeutic strategies may be of great value.…”
Section: Vista Expression In Tumor‐infiltrating Immune Cellsmentioning
confidence: 82%
“…This has been demonstrated in gastric cancer , ovarian cancer , colorectal cancer and primary oral squamous cell mesothelioma . Interestingly, in non‐small‐cell lung cancer (NSCLC) and hepatocellular carcinoma (HCC), tumor cell expression appears to be associated with improved objective survival (OS) . Currently, it is not clear if and how VISTA expression induced in CD45‐negative cells might be supportive for anti‐tumor immunity.…”
Section: Vista Expression In On Non‐hematopoietic Cells In Cancermentioning
confidence: 99%
“…Samples were considered positive for B7-H3 and B7-H4 when ≥5% of the TCs expressing these proteins at any intensity; the 5% cut-off was chosen based on a previous publication [15]. As VISTA expression on TCs and tumourassociated immune cells (TAICs) may have distinct prognostic values [16][17][18], we evaluated the expression of VISTA on these cell types separately. TCs and TAICS were each considered VISTA-positive when ≥5% of them were stained for this protein, as described in previous publications [17,18].…”
Section: Immunohistochemistry and Evaluationmentioning
confidence: 99%
“…These studies suggest that VISTA may modulate a novel immune evasion mechanism and is thus a potential target for cancer immunotherapy. VISTA expression in human cancers has been reported in non-small cell lung cancer (NSCLC), hepatocellular carcinoma, colorectal carcinoma, oral squamous cell carcinoma, gastric carcinoma, acute myeloid leukemia, and gestational trophoblastic neoplasia [13][14][15][16][17][18][19][20][21]. Mulati et al also found that VISTA was highly expressed in human ovarian and endometrial cancers [20].…”
Section: Introductionmentioning
confidence: 98%